Organic Wood Dust Exposure as a Risk Factor for Lung Function Disorders in Workers : Systematic Review - Alifia Intan Berlian; Onny Setiani; Sulistiyani Sulistiyani (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Wood dust is wood particles that result from wood processing and handling. The level of fine dust in the work environment can expose to workers breathing and cause lung function disorders. Obstructive lung function disorders, namely blockages that make it difficult for air to escape from the lungs, resulting in a decrease in airflow velocity. The purpose of this systematic review was to determine wood dust exposure and risk factors for impaired lung function for workers. Article searches carried out through the Portal Garuda Indonesia, PubMed, Scopus, ProQuest, and Google Scholar. There are 9 articles reviewed. Exposure to wood dust was assessed as a significant risk factor for impaired lung function in workers as seen from the statistical analysis results in each study showing that the p-value < 0.05. The risk factors that were stated to have a significant relationship were the concentration of wood dust, gender, work location, use of personal protective equipment (mask), length of work, and smoking habits. Exposure to wood dust increases the risk of impaired lung function in workers, with dust levels ranging from 1.15 mg/m3– 24 mg/m3.